2009
DOI: 10.1016/j.vetimm.2008.10.319
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression of a novel marsupial cathelicidin from the tammar wallaby (Macropus eugenii)

Abstract: Cathelicidins are important components of the innate immune system and have been identified in skin and epithelia of a range of mammals. In this study molecular techniques, including RACE-PCR, were used to identify the full cDNA sequence of a cathelicidin gene, MaeuCath8, from the Australian marsupial, the tammar wallaby, Macropus eugenii. This cathelicidin was not homologous to other such genes previously isolated from a tammar wallaby mammary gland EST library, however, it did contain 4 conserved cysteine re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Early studies on some innate mechanisms, including the composition of the blood of pouch young (Block, 1964;Yadav, 1972;Basden, 1996), the composition of the commensal flora of the gut (Lentle, 2006;Chhour et al, 2010), expression of HLA-DR in the skin of newborn opossums (Coutinho et al, 1995) and the expression of antimicrobial peptides (Carman et al, 2008(Carman et al, , 2009Daly et al, 2008) has laid the foundation for our current understanding of the development of innate immune protection in pouch young marsupials. Further, research on the timing of the development of the innate immune system and early immune protection in marsupials is required.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Early studies on some innate mechanisms, including the composition of the blood of pouch young (Block, 1964;Yadav, 1972;Basden, 1996), the composition of the commensal flora of the gut (Lentle, 2006;Chhour et al, 2010), expression of HLA-DR in the skin of newborn opossums (Coutinho et al, 1995) and the expression of antimicrobial peptides (Carman et al, 2008(Carman et al, , 2009Daly et al, 2008) has laid the foundation for our current understanding of the development of innate immune protection in pouch young marsupials. Further, research on the timing of the development of the innate immune system and early immune protection in marsupials is required.…”
Section: Discussionmentioning
confidence: 99%
“…Carman et al () identified a novel cathelicidin (MaeuCath8) in the tammar wallaby. Expression of this antimicrobial peptide was examined from birth to adulthood.…”
Section: Skinmentioning
confidence: 99%
See 2 more Smart Citations
“…Determining how these altricial young are immunologically protected is of great interest, which has led to studies of the maternal contribution to both pre-and postnatal protection through such mechanisms as maternal milk Demmer, 1999, 2000;Joss et al, 2007Joss et al, , 2009 and pouch secretions [Ambatipudi et al, 2007[Ambatipudi et al, , 2008. Most recently there has been an especial focus on the innate immune system, including a number of antimicrobial peptides -primarily cathelicidins [Carman et al, 2008[Carman et al, , 2009Daly et al, 2008].…”
mentioning
confidence: 99%